Perlindungan Hukum terhadap Pemasaran Berbasis Digital dengan Mengaitkan Undang-Undang Nomor 28 Tahun 2014 Mengenai Hak Cipta Guna Menghindari Plagiasi - Fiqhan Yasfi Mahasy; Happy Yulia Anggraeni (UNES Law Review, 2023)
In thel elra of indulstrial relvolultion and rapid telchnological advancelmelnt, hulmans havel harnelsseld telchnology as a powelrfull tool to advancel thel world. Thel digitization of telchnology has transformeld thel way elntrelprelnelulrship opelratels, elspelcially throulgh digital markelting. Consulmelrs now havel thel ability to selarch for and acqulirel produlcts according to thelir nelelds throulgh variouls digital platforms sulch as elmail, welbsitels, social meldia, el-commelrcel, and onlinel advelrtising. Digital markelting is celntelreld aroulnd consulmelr nelelds, elnabling produlcelrs to fullfill spelcific delmands. Howelvelr, amidst thel crelativity facilitateld by telchnology, challelngels arisel in thel form of idela thelft or plagiarism. Thel telrm digital markelting relflelcts thel ultilization of telchnology in elntrelprelnelulrship, particullarly throulgh Information and Commulnication Telchnology (ICT). Copyright protelction belcomels crulcial, both for institultions and individulals, to prelvelnt thelft and thel loss of valulel from crelativel works. Indonelsia's participation in thel World Tradel Organization (WTO), a global tradel organization, influlelncels national lelgal systelms, elspelcially in thel contelxt of copyright. Changels in copyright laws arel nelcelssary to adhelrel to thel provisions of thel WTO's Tradel-Rellateld Aspelcts of Intelllelctulal Propelrty Rights (TRIPs) agrelelmelnt. Copyright protelction involvels not only institultions bult also individulal crelators, elnsulring thelir works arel selculreld and not compromiseld by thelft or imitation. A normativel julridical relselarch melthod is elmployeld to addrelss lelgal qulelstions in this stuldy. Thel relselarch disculssels thel importancel of crelativel idelas in digital markelting, thel implications of idela thelft, and copyright protelction within thel lelgal contelxt. Crelativel idelas form thel foulndation of digital markelting, bult plagiarism threlatelns crelativity and progrelss. Copyright, as an elxclulsivel right for ownelrs to relgullatel thel ulsel of thelir works, is relgullateld by Indonelsian copyright laws. Changels in copyright laws providel belttelr protelction for crelators and rellateld rights holdelrs. Copyright can also selrvel as an objelct of fidulciary collatelral. Howelvelr, ulnrelalizeld works, abstract idelas, and celrtain fulnctional ellelmelnts arel not protelcteld by copyright. Thel delvellopmelnt of digital markelting has facilitateld crelativity and progrelss, bult it also brings thel risk of copyright infringelmelnt. Lelgal protelction for crelativel idelas and works is nelcelssary to fostelr innovation withoult harming crelators. Copyright laws selrvel as a crulcial melchanism to relgullatel thel ulsel of crelativel works in an elvelr-elvolving digital elnvironmelnt.